Chemical-mineralogical characterization of copper smelting flue dust (2014)
In pyrometallurgical processing of copper, 5-10 wt-% of concentrates fed to smelting furnaces are released in the form of flue dust, which contains most of the impurities that pollute products and effluents as well as very significant amounts of copper. Consequently, these dusts cannot be disposed of as an industrial waste and must be treated to recover the copper in order to assure efficient processing. Better process designs needs precise dust characterization. The present study is aimed at generating useful physical, chemical and morphological information of copper smelting flue dust for samples from the gas handling system of a flash smelting furnace. The analyses showed that copper and iron are mainly found in water-soluble phases like chalcantite and chalcocyanite; the water-insoluble fraction contains largely hematite and magnetite; the presence of delafossite is likely. Part of the copper detected in the insoluble fraction is also associated to iron in form of spinel.